Digital Entrepreneurship and its impact on Enhancing the Competitiveness Capability of Banks: Applied Research in a Number of Private Iraqi Commercial Banks (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aimed to measure the impact of the dimensions of Digital Entrepreneurship represented by (digital knowledge, digital business environment, digital finance, digital leadership, digital entrepreneurial culture), in enhancing the Competitiveness Capability of banks in its dimensions represented by (strategic creativity, strategic flexibility, competitive position), as the research problem was defined by the main question which is (Does Digital Entrepreneurship have a significant impact in enhancing the Competitiveness of the banks studied?), The research adopted the descriptive analytical approach, and the questionnaire was used as a main tool in collecting data, as the sample studied was (187) officials from the community numbering (199) officials in job positions (Director General, Director General, Department Director, Head of Department, Head of Department, Division Manager, Unit Manager), in private Iraqi commercial banks represented by (Baghdad Bank, Iraqi Investment, United Investment, Gulf Commercial, Ashur International Investment, Mansour Investment), and the data were analyzed based on statistical programs (SPSS v.28), in calculating (weighted arithmetic mean, standard deviation, relative importance, coefficient of variation, and simple regression equation, corrected interpretation coefficient AR2, t-test, f-test), and the research reached a set of results, the most prominent of which were: There is a significant impact of Digital Entrepreneurship in enhancing the Competitiveness  Capability of banks, as the dimensions of Digital Entrepreneurship were able to explain the changes and deviations that occurred in enhancing the Competitiveness Capability of banks by a percentage of (76.2%).